Volatilização de clomazone e ocorrência de agrotóxicos e hormônios esteróides na água potável e da chuva de regiões orizícolas do Sul do Brasil - Schreiber, Fábio (2012)
The pesticides used in paddy rice fields, depending phisichochemical characteristics, can on volatilize, making the atmosphere of the likely fate of those losses. The study of pesticide fate in different environmental conditions is essential to understand the dynamics in the soil and also for the development technology to reduce this problem. The objectives of this study were: (i) to conduct a literature review of the main factors affecting the pesticides volatilization (Chapter 1), (ii) to evaluate the relative volatility of different formulations of clomazone (Chapter 2), (iii) and to evaluate injuries caused by different formulations of clomazone in the vapor phase under field conditions in sorghum (Chapter 3), (iv) to monitor the occurrence of steroid hormones and pesticides in drinking water and rain on orizícolas South regions of Brazil (Chapter 4). With the results we conclude: on Chapter II, among the species evaluated, sorghum is the most sensitive to clomazone present in the vapor phase (volatilized) followed by corn and rice. The melon, cucumber and rice (with dietholate) are not good indicators of the presence of this herbicide in the air. The formulation Gamit CS 360® is the one that causes less injury in the species selected as bioindicators (sorghum, maize and rice) compared formulations Gamit 500 EC® and Gamit Star®. Gamit 500 EC® and Gamit Star® showed no significant difference in volatilization potential. On champter III, among the formulations evaluated, Gamit 360 CS® apparently volatilize less and causes less injury to sorghum plants under field conditions when compared to formulations Gamit 500 EC® and Gamit Star®. Gamit 500 EC® and Gamit Star® showed no significant difference in the potential injury to sorghum under field conditions. Sorghum plant injury was higher when plants were closer to the point of application, and along to the rows towards the predominant wind. On champter IV that bentazone, clomazone and imazapic were detected in samples of rainwater and drinking water during the monitoring period in southern Brazil, demonstrating the potential of contamination of these herbicides. The herbicide bentazone was the highest frequency and concentrations in samples of rainwater and drinking water. With the exception of the Coastal Plain Outside the Patos Lagoon (Porto Alegre), all regions monitored had at least one type of pesticide detected in samples of rainwater. The number of samples with detection of herbicides, both for rainwater and for drinking water, was higher in 2nd time, ie during the cultivation of rice.